Close Interspecies Interactions between Prokaryotes from Sulfureous Environments - Müller, Johannes; Overmann, Jörg (Frontiers in Microbiology, 2011)
Green sulfur bacteria are obligate photolithoautotrophs that require highly reducing conditions for growth and can utilize only a very limited number of carbon substrates. These bacteria thus inhabit a very narrow ecologic niche. However, several green sulfur bacteria have overcome the limits of immobility by entering into a symbiosis with motile Betaproteobacteria in a type of multicelllular association termed phototrophic consortia. One of these consortia, “Chlorochromatium aggregatum”, has recently been established as the first culturable model system to elucidate the molecular basis of this symbiotic interaction. It consists of 12-20 green sulfur bacteria epibionts surrounding a central, chemoheterotrophic betaproteobacterium in a highly ordered fashion. Recent genomic, transcriptomic, and proteomic studies of "C. aggregatum" and its epibiont provide insights into the molecular basis and the origin of the stable association between the two very distantly related bacteria. While numerous genes of central metabolic pathways are upregulated during and hence involved in the specific symbiosis, only a limited number of unique putative symbiosis genes have been detected in the epibiont. Green sulfur bacteria therefore are preadapted to a symbiotic lifestyle. The metabolic coupling between the bacterial partners appears to involve amino acids and highly specific ultrastructures at the contact sites between the cells. Similarly, the interaction in the equally well studied archaeal consortia consisting of Nanoarchaeum equitans and its host Ignicoccus hospitalis is based on the transfer of amino acids while lacking the highly specialized contact sites observed in phototrophic consortia.